The medical mind of Ibn Kholdoun in Al Mogademah (The Prefacet) - Adwan, Mezyed (Advances in Social Sciences Research Journal, 2021)
The title of this research paper is “Ibn Khaldoun’s Medical Mind. This paper discusses two general concepts related to medicine , the concept of delivery and medicine in general. Ibn Kaldoun discusses the nature of science as viewed by Ibn Khaldoun, the anatomy and physiology of digestive system and its accessories , the liver,ducts m secreation, diagestive gland as well as food digestion and absorption, delivery process and some issues related to the delivery and dilevery process as well as the role of the Midwife. Ibn Khaldoun defined the "Medicine"and medical profession and delivery . He also discussed some other concepts as disease, and the causes of illness. Ibn Khaldoun stressed the importance of exercise, diet and environmental factors on healthy living.Ibn Khaldoun functioned these factors in treatment of diseases.